Two-dimensional growth, anisotropic polaron transport and magnetic phase segregation in epitaxial Nd0.52Sr0.48MnO3 films - Prokhorov, V.G.; Bukin, G.V.; Nikolaenko, Yu.M.; Medvedev, Yu.V.; Paschenko, A.V.; Levtchenko, G.G.; Svetchnikov, V.L.; Lee, Y.P.; Park, J.S.; Eom, T.W.; Kim, J.M.; Kaminsky, G.G.; et al. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Nd0.52Sr0.48MnO3 films have been prepared by dc magnetron sputtering on LaAlO3 (001) and SrTiO3 (011) single-crystalline substrates with an additional annealing for the lattice strain relaxation. Even though thatthe Nd0.52Sr0.48MnO3 films were deposited simultaneously on different substrates at the same deposition ratethey differ in the thickness by ≃√2̅. The observed difference in the thickness is explained by the twodimensional(layer-by-layer) growth of film rather than a difference in the growth rate, controlled by the crystal orientation of substrate. The analysis of the optical and transport properties reveals that the observed anisotropy in the polaron motion is governed by a strong anisotropy of the trapping energy rather than the polaron formation one. It was shown that the deposited Nd0.52Sr0.48MnO3 films manifest a magnetic behavior typical for twophases magnetic systems and must be considered as an assembly of interacting magnetic clusters.